2017
DOI: 10.21608/ejfsat.2017.46106
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Monosodium Glutamate on Male Rat Reproductive System and Effect of Curcumin and Propolis Co-Administeration

Abstract: The safety of monosodium glutamate (MSG) usage has generated much controversy locally and globally. MSG is known to affect the structure and function of male reproductive system as well as fertility. The aim of the present work was to study the toxic effect of MSG on reproductive system of adult male albino rats and to determine the possibility to reverse this effect using curcumin and propolis. Seventy sexually mature male albino rats were used for this study and divided into 7 groups. The first 3 were contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…In the present study, pregnant females in the different experimental treated groups showed a significant increase in body weight gain during the gestation period. This result agrees with Tala’a ( 2019 ), Mohamed et al ( 2017 ), and Savcheniuk et al ( 2014 ). Moreover, Abd El-Aziz et al ( 2014 ) found prolonged administration of MSG causes an initial increase in weight gain followed by terminal suppression and independent of food consumption.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, pregnant females in the different experimental treated groups showed a significant increase in body weight gain during the gestation period. This result agrees with Tala’a ( 2019 ), Mohamed et al ( 2017 ), and Savcheniuk et al ( 2014 ). Moreover, Abd El-Aziz et al ( 2014 ) found prolonged administration of MSG causes an initial increase in weight gain followed by terminal suppression and independent of food consumption.…”
Section: Discussionsupporting
confidence: 92%
“…Dosing of heavy metals mixture produced lower level of glutathione peroxidase (GPx) in liver (p < 0.0001) and kidney (p < 0.001) tissues at heavy metals group in comparison with control group, this could probably due to the utilization of its defense mechanism against toxic metals within these organs as a result of ROS generation; such suggestion is matched with Ercal et al, (2001); Saxena et al, (2005) and Bas & Kalender (2016). However, rats that exposed to toxic metals and treated with propolis exhibited signi cant improving in the activities of GPx in livers (p < 0.001) as well kidney (p < 0.01) when compared with heavy metals group; that issue clarify the protective role of propolis in recovering the affected tissues of liver and kidney as healthy rats through reducing combined toxicity of investigated metals; these ndings were corroborated very well with Salama & El-Bahr, (2007);Bhadauria, (2012) and Mohamed et al, (2017). Additionally, after propolis treatment, both livers and kidneys of rats exhibited statistical improving (p < 0.0001 and p < 0.01, respectively) in the activities of glutathione reductase (GR) which previously showed signi cant decrease among the livers (p < 0.0001) and kidneys (p < 0.001) of rats at heavy metals group comparing to control, this may attributed to the ability of investigated metals to overcome the vital role of GR in order to interfere with the disul de bond of glutathione enzyme and inhibits its activity therefore, prevent the optimal balance and make cells more susceptible to oxidative damage; our observations are in the same way of those obtained by; Ercal et al, (2001) and Jomova & Valko, (2011).…”
Section: -4-antioxidant Enzymes and Propolissupporting
confidence: 74%
“…The use of multiple antioxidant and healing chemotherapeutic agents can favor the treatment of skin lesions. Recent studies have shown the synergistic effects of propolis extract (PRP) and curcumin (CUR) increasing the therapeutic efficiency, mainly due to their antioxidant, anti-inflammatory and antimicrobial activities [34,35]. The PRP is a complex mixture of vegetable substances used to protect the comb by sealing gaps and keeping insects and microorganisms away [36,37].…”
Section: Introductionmentioning
confidence: 99%